2018
DOI: 10.5539/ijef.v10n12p87
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and Economic Growth: A Comparative Empirical Analysis Between Cameroon and the Ivory Coast

Abstract: Inflation is the main concern of developing Countries and particularly in Ivory Coast, a leading West Africa French speaking Country. The objective of this study is to make a comparative analysis of the effect of inflation on growth between Cameroon, a French speaking Central Africa Country where inflation is not a big concern and Ivory Coast. Using the Least Squares methodology, we find that inflation has no effect on economic growth in Cameroon during the study period. However, it has a negative and signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…The bipolar divides has been between the role and causality of inflation on macroeconomic performance (Doguwa, 2012;Friedman, 1973;Stockman, 1981). The empirical findings of several studies are also inconclusive, while some studies found positive relationship (Osuala, & Onyeike, 2013); others like Ngouhouo and Nkemgha, (2018) found a negative relationship between these two macroeconomic variables.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The bipolar divides has been between the role and causality of inflation on macroeconomic performance (Doguwa, 2012;Friedman, 1973;Stockman, 1981). The empirical findings of several studies are also inconclusive, while some studies found positive relationship (Osuala, & Onyeike, 2013); others like Ngouhouo and Nkemgha, (2018) found a negative relationship between these two macroeconomic variables.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…However, there was no short run causality between inflation and economic growth. Ngouhouo and Nkemgha (2018) examine a comparative analysis of the effect of inflation on growth between Cameroon, French speaking Central Africa Country where inflation is not a big concern and Ivory Coast. Using the Least Squares methodology, they found that inflation have no effect on economic growth in Cameroon during the study period.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The inflation (Inf) is measure by the consumer price index. According to Ngouhouo and Nkemgha (2018) inflation is deleterious to economic growth.…”
Section: Data and Variables Definitionmentioning
confidence: 99%